Design and Development of a Flood Detection Device for Drainage Systems Utilizing Float Switch Water Level Sensors - Yosi Riduas Hais; Edi Saputra; Aldo Tri Ilham Zk; Andre Raboula (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2024)
Indonesia ranks second in Asia Pacific in the list of the highest number of deaths due to natural disasters. In a year, more than 300 flood events occur, resulting in large losses, environmental damage and even loss of life. To overcome this problem, it is necessary to design a tool for monitoring water levels and rainfall. This research aims to design a flood detection system using the fuzzy method and using a float switch water level sensor. The results of the research show that this system can monitor water levels and rainfall using a web server. In the first test, it produces a fuzzy warning level in a safe condition. In the second test, the water level reached 51 cm with rainfall of 0.47 mm, and the fuzzy warning level was in a safe condition. Finally, in the third test, the average water level reached 99 cm with rainfall of 0.69 mm, resulting in a fuzzy warning level in an alert state. It can be concluded that this system needs to be improved in quality by adding items to the system.